Brass alloy and preparation method thereof

A brass alloy with controlled carbon, copper, arsenic, antimony, and iodine composition, along with specific microstructural phases, addresses machinability and corrosion issues, offering superior performance for environmentally friendly applications.

CN119242983APending Publication Date: 2025-01-03JINTIAN COPPER GROUP CORP NINGBO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411366866.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing lead-free brass alloys suffer from poor machinability, low wear resistance, and vulnerability to dezincification corrosion, limiting their application in fields requiring high-performance materials that meet environmental protection standards.

Method used

A brass alloy comprising specific percentages of carbon (C), copper (Cu), arsenic (As), antimony (Sb), iodine (I), and unavoidable impurities, with a microstructure including a matrix phase and second phases like C phase, BN, and BAl2, which enhances corrosion resistance and wear resistance through electrochemical protection and grain refinement.

Benefits of technology

The alloy exhibits excellent processing performance, corrosion resistance, and wear resistance, meeting market demands for lead-free and environmentally friendly materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242983A_ABST
    Figure CN119242983A_ABST
Patent Text Reader

Abstract

The brass alloy comprises 0.05% < = mC < = 1%, 61.5% < = mCu < = 63.5%, 0.02% < = mAs < = 0.15% of As, 0.02% < = mSb < = 0.1%, 0.02% < = mI < = 0.1%, Zn and inevitable impurities. The Zn and the impurities are the balance components in the brass alloy; the brass alloy comprises a matrix phase and a second phase, wherein the matrix phase comprises an alpha phase, an islanding-shaped beta phase and an equiaxed crystal-shaped beta'phase, and the beta phase and the beta 'phase are divided by the alpha phase; wherein the second phase comprises a C phase, BN and BAl2, and the C phase is uniformly distributed in the matrix phase. The mass percent of Pb in the brass alloy is lower than 0.2%, and the brass alloy is excellent in processability, corrosion resistance and wear resistance and meets the requirements of the current market for lead-free environment-friendly materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgical materials, and in particular to a brass alloy and a preparation method thereof. Background Art

[0002] Brass, as an alloy of copper and zinc, has been widely used in industrial and decorative fields due to its beautiful appearance and excellent physical and chemical properties. Although traditional copper-zinc binary brass has good comprehensive properties, its processing performance is insufficient, which limits its application in a wider range of fields. In order to improve this defect, a small amount of lead is usually added to brass to improve its machining performance. However, lead is a toxic heavy metal that has potential harm to both the human body and the environment. Therefore, as people's awareness of health and environmental protection increases, the use of leaded brass has been increasingly restricted. Many countries and regions have begun to formulate laws and regulations to restrict or prohibit the use of lead in industrial products, especially in those products that come into direct contact with the human body.

[0003] With the trend of lead-free, some lead-free brass products have appeared on the market, such as ordinary lead-free brass (H59, H62, H65 series) and special lead-free brass (such as C46500 tin brass and CW511L arsenic brass). Although these lead-free brasses meet environmental protection requirements to a certain extent, their application is still limited. The main problems include poor machinability and low wear resistance, as well as vulnerability to dezincification corrosion. After comparing the existing lead-free brass materials, it was found that arsenic brass performed best in dezincification corrosion resistance, but its machinability and wear resistance still need to be improved.

[0004] As the requirements for lead-free are deepening, the demand for lead-free brass in the fields of home furnishing, bathroom, electronic machinery, etc. is growing. This requires material scientists and engineers to develop new brass alloys and their preparation methods to meet the market demand for high-performance brass. The new brass alloy needs to have good machining performance, wear resistance and corrosion resistance, especially the ability to resist dezincification corrosion, while maintaining the excellent physical and chemical properties of brass.

[0005] Therefore, there is an urgent need for a brass alloy and a preparation method thereof to address the deficiencies of existing brass alloys in processing performance, wear resistance and corrosion resistance, and to meet increasingly stringent environmental protection requirements and market demands. Summary of the invention

[0006] The object of the present invention is to provide a brass alloy and a preparation method thereof in view of the deficiencies in the prior art.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] The first aspect of the present invention is to provide a brass alloy, comprising: C: 0.05% ≤ m C ≤1%、Cu:61.5%≤m Cu ≤63.5%、As:0.02%≤m As ≤0.15%, Sb: 0.02%≤m Sb ≤0.1%、I:0.02%≤m I ≤0.1%, Zn, and unavoidable impurities;

[0009] Among them, m C represents the mass percentage of the C in the brass alloy, m Cu represents the mass percentage of Cu in the brass alloy, m As represents the mass percentage of As in the brass alloy, m Sb represents the mass percentage of Sb in the brass alloy, m I represents the mass percentage of I in the brass alloy, and the Zn and the impurities are the remaining components in the brass alloy;

[0010] Furthermore, the brass alloy comprises: a matrix phase and a second phase;

[0011] The matrix phase includes: an α phase, an island-shaped β phase, and an equiaxed crystal-shaped β' phase, and the β phase and the β' phase are separated by the α phase;

[0012] The second phase includes: C phase, BN, and BAl2, and the C phase is uniformly distributed in the matrix phase.

[0013] The present invention can improve the electrode potential of the material by introducing arsenic, antimony and iodine, and effectively inhibit the Cu 2+ The formation of As2O3 prevents the electrochemical corrosion of the α phase, and the As2O3, Sb2O3 and I2O3 formed on the surface of the α phase provide protection to achieve better corrosion resistance.

[0014] As+Cu 2+ →As 3+ +Cu +

[0015] Sb+Cu 2+ →Sb 3+ +Cu +

[0016] I+Cu 2+ →I 3+ +Cu +

[0017] The α phase of the present invention will precipitate β phase from the surface, and the β phase will decompose into isolated equiaxed crystal β' phase. At the same time, the β phase and the β' phase are divided by the α phase, thereby blocking the corrosion channel to eliminate the corrosion effect of the unstable β phase and improve the corrosion resistance of the alloy.

[0018] α+β→β→β+β'→α+β+β'

[0019] The C phase of the present invention is evenly distributed in the matrix phase, and plays a role in lubrication and chip breaking during the cutting process; and the formation of BN and BAl2 promotes non-uniform nucleation, increases the number of grains, thereby achieving grain refinement, and due to the compactness of the grain structure, blocks possible corrosion channels, thereby improving the lubrication and wear resistance of the alloy.

[0020] Preferably, the impurities include: Fe:m Fe <0.1%, and Pb:m Pb <0.2%;

[0021] Among them, m Fe represents the mass percentage of the Fe in the brass alloy, m Pb represents the mass percentage of the Pb in the brass alloy.

[0022] Preferably, the particle size of the C phase is 1 nm-200 nm.

[0023] The mass percentage of C in the brass alloy of the present invention is controlled within the range of 0.05%-1%, and the particle size of the C phase is controlled within the range of 1nm-200nm to ensure the toughness and elongation of the alloy.

[0024] The second aspect of the present invention is to provide a method for preparing the brass alloy as described above, the steps comprising:

[0025] After the raw materials, the graphene copper alloy, and the refiner are smelted, the materials are sequentially subjected to casting, single-hole extrusion, and stretching or drawing to obtain the brass alloy.

[0026] Preferably, the steps include:

[0027] Step 1: After melting the processed recycled materials, graphene copper alloy, copper powder, arsenic ingots, antimony ingots, and copper iodide, the materials are slag-removed;

[0028] Step 2: Take samples of the materials and perform component tests on the samples to determine whether the samples meet the following requirements:

[0029] m Fe <0.1%, 61.5%≤m Cu≤63.5%, 0.02%≤m As ≤0.15%, 0.02%≤m Sb ≤0.1%, 0.02%≤m I

[0030] ≤0.1%, m Pb <0.2%;

[0031] If not, add the corresponding materials and return to step 1;

[0032] If satisfied, proceed to step 3;

[0033] Step 3: adding a refining agent and refining the material; adding a refiner and refining the material;

[0034] Step 4: sequentially subjecting the material to casting, single-hole extrusion, and stretching or drawing to obtain the brass alloy.

[0035] The graphene copper alloy of the present invention is used to form the aforementioned C phase.

[0036] Preferably, the mass percentage of graphene in the graphene copper alloy is 0.01%-2%.

[0037] Preferably, the refiner includes: ammonium chloride, borax, ammonium carbonate, and potassium fluoroborate.

[0038] The refiner of the present invention is used to form the aforementioned BN and the aforementioned BAl2.

[0039] NH4Cl+Na2B4O7·10H2O+(NH4)2CO3→BN+NaCl+B2O3+H2O+CO2

[0040] KBF4+Al→KAlF4+BAl2

[0041] Preferably, the refiner comprises, by mass percentage, 10%-50% of ammonium chloride, 30%-50% of borax, 10%-50% of ammonium carbonate, and 5%-20% of potassium fluoroborate.

[0042] Preferably, the extrusion ratio of the single hole extrusion process is 25-350.

[0043] The single hole extrusion of the present invention is used to form the aforementioned β' phase.

[0044] Preferably, the cooling water tank used in the single-hole extrusion process comprises: a tank body, and a water flow distribution plate obliquely arranged inside the tank body; wherein,

[0045] The bottom end of the trough body is provided with a water inlet, the top end of the trough body is provided with a water outlet, and a notch connected to a single-hole extruder is provided on one side of the trough body close to the water outlet;

[0046] Wherein, the water inlet and the water outlet are respectively arranged on both sides of the main body, and a water seal ring is arranged on the notch;

[0047] The water flow distribution plate is a plate-like structure with a plurality of through holes evenly opened thereon, and the water flow distribution plate divides the interior of the tank into a first cavity and a second cavity;

[0048] The volume of the first cavity is the same as that of the second cavity, the water inlet is connected to the first cavity, the first cavity is connected to the second cavity through a plurality of through holes, and the second cavity is connected to the water outlet;

[0049] The brass alloy rod obtained by the single-hole extruder enters the second cavity through the notch for cooling.

[0050] The water flow uniform distribution plate of the present invention can make the temperature of cooling water in the cooling water tank body tend to be consistent, so as to improve the stability of the performance of the brass alloy rod.

[0051] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:

[0052] The mass percentage of Pb in the brass alloy of the present invention is less than 0.2%, and the brass alloy has excellent processing performance, corrosion resistance and wear resistance, thus meeting the current market demand for lead-free and environmentally friendly materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is a schematic diagram of the structure of the cooling water tank in the present invention;

[0054] Figure 2 It is a schematic diagram of the structure of the water flow uniform distribution plate in the present invention;

[0055] Among them, the reference numerals include: brass alloy rod 0; tank body 1; water inlet 11; water outlet 12; notch 13; water seal ring 131; first cavity 14; second cavity 15; water flow uniform distribution plate 2. DETAILED DESCRIPTION

[0056] The specific embodiments of the present invention will be described in detail below.

[0057] Unless otherwise defined, technical or scientific terms used in the claims and the specification shall have the common meanings understood by persons having ordinary skills in the technical field to which the present invention belongs.

[0058] The words "include" or similar words used in the patent application specification and claims of the present invention mean that the items appearing before "include" include the items listed after "include" or their equivalents, and do not exclude other items.

[0059] The numerical values ​​mentioned in the present invention include all numerical values ​​that increase from low to high by one unit, assuming that there are at least two units between any lower value and the higher value. For example, if a component or a physical quantity is said to be from 1 to 100, 10 to 90 is more preferred, and 20 to 80 is the most preferred, it is intended to express that values ​​such as 5 to 95, 14 to 76, 23 to 67, 32 to 58, 41 to 49 are clearly listed in this specification; for values ​​less than 1, 0.0001, 0.001, 0.01 or 0.1 are considered to be more suitable as a unit. The above examples are for illustrative purposes only. In fact, all numerical combinations between the lowest value and the highest value listed are deemed to be clearly listed in this specification in a similar manner.

[0060] Example 1

[0061] This embodiment first provides a graphene copper alloy, wherein:

[0062] The mass percentage of graphene in the graphene copper alloy is 0.01%-2%.

[0063] It is obvious that any graphene copper alloy with a graphene mass percentage of 0.01%-2% can be used to form the aforementioned C phase.

[0064] This embodiment secondly provides a refiner, wherein:

[0065] In terms of mass percentage, the refiner includes: 20% ammonium chloride, 30% borax, 30% ammonium carbonate, and 20% potassium fluoroborate.

[0066] This embodiment finally provides a cooling water tank, wherein:

[0067] like Figure 1 As shown, the cooling water tank comprises: a tank body 1, and a water flow distribution plate 2 obliquely arranged inside the tank body 1; wherein,

[0068] The bottom end of the tank body 1 is provided with a water inlet 11, the top end of the tank body 1 is provided with a water outlet 12, and a notch 13 connected to a single-hole extruder is provided on one side of the tank body 1 close to the water outlet 12;

[0069] The water inlet 11 and the water outlet 12 are respectively arranged on both sides of the main body 1, and a water seal ring 131 is arranged on the notch 13;

[0070] like Figure 2 As shown, the water flow uniform distribution plate 2 is a plate-like structure with a plurality of through holes evenly opened thereon, and the water flow uniform distribution plate 2 divides the interior of the tank body 1 into a first cavity 14 and a second cavity 15;

[0071] The volume of the first cavity 14 is the same as that of the second cavity 15, the water inlet 11 is connected to the first cavity 14, the first cavity 14 is connected to the second cavity 15 through a plurality of through holes, and the second cavity 15 is connected to the water outlet 12;

[0072] The brass alloy rod 0 obtained by the single-hole extruder enters the second cavity 15 through the notch 13 for cooling.

[0073] Example 2

[0074] This embodiment provides a method for preparing a brass alloy, the steps comprising:

[0075] Step 1: Melting the processed recycled materials, graphene copper alloy, copper powder, arsenic ingots, antimony ingots, and copper iodide;

[0076] Wherein, the mass percentage of the processed recycled materials in all materials is 60%;

[0077] Wherein, the graphene copper alloy is as described in Example 1;

[0078] Among them, the melting temperature is higher than 1080°C;

[0079] Carry out slag treatment on materials;

[0080] Step 2: Take samples of the materials and perform component tests on the samples to determine whether the samples meet the following requirements:

[0081] m Fe <0.1%, 61.5%≤m Cu ≤63.5%, 0.02%≤m As ≤0.15%, 0.02%≤m Sb ≤0.1%, 0.02%≤m I

[0082] ≤0.1%, m Pb <0.2%;

[0083] If not, add the corresponding materials and return to step 1;

[0084] If satisfied, proceed to step 3;

[0085] Step 3: adding a refining agent and refining the material;

[0086] Add refiner and refine the material;

[0087] Wherein, the refiner is as described in Example 1;

[0088] Keep at 1000℃ for 10min-15min;

[0089] Spray fire at 1120℃ for 20s-25s;

[0090] Control the temperature to 1050℃-1100℃ and proceed to step 4;

[0091] Step 4: performing casting treatment, single-hole extrusion treatment, and stretching treatment on the material in sequence to obtain the brass alloy;

[0092] The casting process adopts a φ180mm crystallizer, the casting temperature is 1100°C, the pulling speed is 76mm / min, the inlet and outlet temperature difference of the primary cooling water is 25°C-38°C, the distance between the secondary water ring and the crystallizer outlet is 70mm, the temperature of the ingot out of the crystallizer is 620°C, and the temperature of the ingot after water cooling is 20°C;

[0093] The single-hole extrusion process uses a 1800t single-hole extruder and a cooling water tank as described in Example 1. The single-hole extrusion obtains a φ20.5mm blank, the extrusion ratio is 77, the extrusion temperature is 720°C, the extrusion speed is 18mm / min, and the flow rate of the cooling water tank is 30m 3 / h;

[0094] The stretching treatment includes: a φ20.5 mm head treatment, a pickling treatment, a φ20 mm stretching treatment, a finishing treatment, and a stress relief annealing treatment at 280° C. for 3 hours.

[0095] The brass alloy prepared in this embodiment includes: C: 0.05% ≤ m C ≤1%、Fe:m Fe =0.06%, Cu:m Cu =61.7%, As:m As =0.14%, Sb:m Sb ≤0.08%、I:m I =0.04%, Pb:m Pb =0.15%, Zn, and unavoidable impurities;

[0096] Among them, m C represents the mass percentage of the C in the brass alloy, m Fe represents the mass percentage of the Fe in the brass alloy, m Cu represents the mass percentage of Cu in the brass alloy, mAs represents the mass percentage of As in the brass alloy, m Sb represents the mass percentage of Sb in the brass alloy, m I represents the mass percentage of I in the brass alloy, m Pb represents the mass percentage of the Pb in the brass alloy, and the Zn and the impurities are the remaining components in the brass alloy;

[0097] At the same time, the grain size is 20μm; the anti-dezincification value is 20μm / 10μm / 25μm / 20μm / 20μm (H), 35μm / 30μm / 25μm / 30μm / 35μm (Z); the cutting performance is good; the friction coefficient is 0.15 (without lubrication), 0.014 (oil lubrication); the corrosion rate is 0.01mm / a (seawater).

[0098] Example 3

[0099] This embodiment provides another method for preparing a brass alloy, the steps comprising:

[0100] Step 1: Melting the processed recycled materials, graphene copper alloy, copper powder, arsenic ingots, antimony ingots, and copper iodide;

[0101] Wherein, the mass percentage of the processed recycled materials in all materials is 60%;

[0102] Wherein, the graphene copper alloy is as described in Example 1;

[0103] Among them, the melting temperature is higher than 1080°C;

[0104] Carry out slag treatment on materials;

[0105] Step 2: Take samples of the materials and perform component tests on the samples to determine whether the samples meet the following requirements:

[0106] m Fe <0.1%, 61.5%≤m Cu ≤63.5%, 0.02%≤m As ≤0.15%, 0.02%≤m Sb ≤0.1%, 0.02%≤m I

[0107] ≤0.1%, m Pb <0.2%;

[0108] If not, add the corresponding materials and return to step 1;

[0109] If satisfied, proceed to step 3;

[0110] Step 3: adding a refining agent and refining the material;

[0111] Add refiner and refine the material;

[0112] Wherein, the refiner is as described in Example 1;

[0113] Keep at 1000℃ for 10min-15min;

[0114] Spray fire at 1120℃ for 20s-25s;

[0115] Control the temperature to 1050℃-1100℃ and proceed to step 4;

[0116] Step 4: performing casting treatment, single-hole extrusion treatment, and stretching treatment on the material in sequence to obtain the brass alloy;

[0117] The casting process adopts a φ180mm crystallizer, the casting temperature is 1100°C, the pulling speed is 76mm / min, the inlet and outlet temperature difference of the primary cooling water is 25°C-38°C, the distance between the secondary water ring and the crystallizer outlet is 70mm, the temperature of the ingot out of the crystallizer is 620°C, and the temperature of the ingot after water cooling is 20°C;

[0118] The single-hole extrusion process uses a 1800t single-hole extruder and a cooling water tank as described in Example 1. The single-hole extrusion obtains a φ35.4mm blank, the extrusion ratio is 26, the extrusion temperature is 690°C, the extrusion speed is 15mm / min, and the flow rate of the cooling water tank is 50m 3 / h;

[0119] The stretching treatment includes: a φ35.4 mm head treatment, a pickling treatment, a φ35 mm stretching treatment, a finishing treatment, and a stress relief annealing treatment at 300° C. for 3 hours.

[0120] The brass alloy prepared in this embodiment includes: C: 0.05% ≤ m C ≤1%、Fe:m Fe =0.08%, Cu:m Cu =62.7%, As:m As =0.14%, Sb:m Sb ≤0.08%、I:m I =0.08%, Pb:m Pb =0.15%, Zn, and unavoidable impurities;

[0121] Among them, m C represents the mass percentage of the C in the brass alloy, m Ferepresents the mass percentage of the Fe in the brass alloy, m Cu represents the mass percentage of Cu in the brass alloy, m As represents the mass percentage of As in the brass alloy, m Sb represents the mass percentage of Sb in the brass alloy, m I represents the mass percentage of I in the brass alloy, m Pb represents the mass percentage of the Pb in the brass alloy, and the Zn and the impurities are the remaining components in the brass alloy;

[0122] At the same time, the grain size is 15μm; the anti-dezincification value is 25μm / 15μm / 20μm / 30μm / 10μm (H), 25μm / 35μm / 35μm / 20μm / 25μm (Z); the cutting performance is good; the friction coefficient is 0.14 (without lubrication), 0.015 (oil lubrication); the corrosion rate is 0.008mm / a (seawater).

[0123] Example 4

[0124] This embodiment provides another method for preparing a brass alloy, the steps comprising:

[0125] Step 1: Melting the processed recycled materials, graphene copper alloy, copper powder, arsenic ingots, antimony ingots, and copper iodide;

[0126] Wherein, the mass percentage of the processed recycled materials in all materials is 60%;

[0127] Wherein, the graphene copper alloy is as described in Example 1;

[0128] Among them, the melting temperature is higher than 1080°C;

[0129] Carry out slag treatment on materials;

[0130] Step 2: Take samples of the materials and perform component tests on the samples to determine whether the samples meet the following requirements:

[0131] m Fe <0.1%, 61.5%≤m Cu ≤63.5%, 0.02%≤m As ≤0.15%, 0.02%≤m Sb ≤0.1%, 0.02%≤m I

[0132] ≤0.1%, m Pb <0.2%;

[0133] If not, add the corresponding materials and return to step 1;

[0134] If satisfied, proceed to step 3;

[0135] Step 3: adding a refining agent and refining the material;

[0136] Add refiner and refine the material;

[0137] Wherein, the refiner is as described in Example 1;

[0138] Keep at 1000℃ for 10min-15min;

[0139] Spray fire at 1120℃ for 20s-25s;

[0140] Control the temperature to 1050℃-1100℃ and proceed to step 4;

[0141] Step 4: performing casting treatment, single-hole extrusion treatment, and drawing treatment on the material in sequence to obtain the brass alloy;

[0142] The casting process adopts a φ180mm crystallizer, the casting temperature is 1100°C, the pulling speed is 76mm / min, the inlet and outlet temperature difference of the primary cooling water is 25°C-38°C, the distance between the secondary water ring and the crystallizer outlet is 70mm, the temperature of the ingot out of the crystallizer is 620°C, and the temperature of the ingot after water cooling is 20°C;

[0143] The single-hole extrusion process uses a 1800t single-hole extruder and a cooling water tank as described in Example 1. The single-hole extrusion obtains a φ10.5mm blank, the extrusion ratio is 293, the extrusion temperature is 720°C, the extrusion speed is 20mm / min, and the flow rate of the cooling water tank is 20m 3 / h;

[0144] The drawing process includes: a φ10.5 mm head making process, a pickling process, a φ10 mm drawing process, and a stress relief annealing process at 300° C. for 3 hours.

[0145] The brass alloy prepared in this embodiment includes: C: 0.05% ≤ m C ≤1%、Fe:m Fe =0.07%, Cu:m Cu =63.2%, As:m As =0.14%, Sb:m Sb ≤0.08%、I:m I =0.08%, Pb:m Pb =0.15%, Zn, and unavoidable impurities;

[0146] Among them, mC represents the mass percentage of the C in the brass alloy, m Fe represents the mass percentage of the Fe in the brass alloy, m Cu represents the mass percentage of Cu in the brass alloy, m As represents the mass percentage of As in the brass alloy, m Sb represents the mass percentage of Sb in the brass alloy, m I represents the mass percentage of I in the brass alloy, m Pb represents the mass percentage of the Pb in the brass alloy, and the Zn and the impurities are the remaining components in the brass alloy;

[0147] At the same time, the grain size is 25μm; the anti-dezincification value is 15μm / 35μm / 30μm / 10μm / 20μm (H), 35μm / 15μm / 30μm / 30μm / 35μm (Z); the cutting performance is good; the friction coefficient is 0.16 (without lubrication), 0.013 (oil lubrication); the corrosion rate is 0.007mm / a (seawater).

[0148] Comparative Example 1

[0149] This comparative example provides a method for preparing a brass alloy, the steps comprising:

[0150] Step 1: Melting the processed recycled materials, copper dust, and arsenic ingots;

[0151] Wherein, the mass percentage of the processed recycled materials in all materials is 60%;

[0152] Among them, the melting temperature is higher than 1080°C;

[0153] Carry out slag treatment on materials;

[0154] Step 2: Take samples of the materials and perform component tests on the samples to determine whether the samples meet the following requirements:

[0155] m Fe <0.1%, 61.5%≤m Cu ≤63.5%, 0.02%≤m As ≤0.15%, m Pb <0.2%;

[0156] If not, add the corresponding materials and return to step 1;

[0157] If satisfied, proceed to step 3;

[0158] Step 3: adding a refining agent and refining the material;

[0159] Keep at 1000℃ for 10min-15min;

[0160] Spray fire at 1120℃ for 20s-25s;

[0161] Control the temperature to 1050℃-1100℃ and proceed to step 4;

[0162] Step 4: performing casting treatment, double-hole extrusion treatment, and stretching treatment on the material in sequence to obtain the brass alloy;

[0163] The casting process adopts a φ180mm crystallizer, the casting temperature is 1100°C, the pulling speed is 76mm / min, the inlet and outlet temperature difference of the primary cooling water is 25°C-38°C, the distance between the secondary water ring and the crystallizer outlet is 70mm, the temperature of the ingot out of the crystallizer is 620°C, and the temperature of the ingot after water cooling is 20°C;

[0164] The double-hole extrusion process uses a 1800t double-hole extruder, and the double-hole extrusion obtains a φ20.5mm blank, with an extrusion ratio of 38.5, an extrusion temperature of 720°C, and an extrusion speed of 18mm / min.

[0165] The drawing process includes: a φ20.5 mm head treatment, a pickling process, a φ20 mm elongation process, a straightening process, and a stress relief annealing process at 300° C. for 3 hours.

[0166] The brass alloy prepared in this embodiment includes: Fe: m Fe =0.07%, Cu:m Cu =62.2%, As:m As =0.14%, Pb:m Pb =0.15%, Zn, and unavoidable impurities;

[0167] Among them, m Fe represents the mass percentage of the Fe in the brass alloy, m Cu represents the mass percentage of Cu in the brass alloy, m As represents the mass percentage of As in the brass alloy, m Pb represents the mass percentage of the Pb in the brass alloy, and the Zn and the impurities are the remaining components in the brass alloy;

[0168] At the same time, the grain size is 45μm; the anti-dezincification values ​​are 85μm / 95μm / 100μm / 110μm / 120μm (H), 75μm / 105μm / 130μm / 180μm / 85μm (Z); the cutting performance is poor; the friction coefficient is 0.4 (no lubrication), 0.06 (oil lubrication); the corrosion rate is 0.04mm / a (seawater).

[0169] In summary, the brass alloy of the present invention has excellent performance in processing performance, corrosion resistance and wear resistance, and meets the current market demand for environmentally friendly materials.

[0170] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.

Claims

1. A brass alloy, characterized in that: Including: C: 0.05% ≤ m C ≤1%、Cu:61.5%≤m Cu ≤63.5%、As:0.02%≤m As ≤0.15%, Sb: 0.02%≤m Sb ≤0.1%、I:0.02%≤m I ≤0.1%, Zn, and unavoidable impurities; Among them, m C represents the mass percentage of the C in the brass alloy, m Cu represents the mass percentage of Cu in the brass alloy, m As represents the mass percentage of As in the brass alloy, m Sb represents the mass percentage of Sb in the brass alloy, m I represents the mass percentage of I in the brass alloy, and the Zn and the impurities are the remaining components in the brass alloy; Furthermore, the brass alloy comprises: a matrix phase and a second phase; The matrix phase includes: an α phase, an island-shaped β phase, and an equiaxed crystal-shaped β' phase, and the β phase and the β' phase are separated by the α phase; The second phase includes: C phase, BN, and BAl2, and the C phase is uniformly distributed in the matrix phase.

2. The brass alloy according to claim 1, characterized in that The impurities include: Fe:m Fe <0.1%, and Pb:m Pb <0.2%; Among them, m Fe represents the mass percentage of the Fe in the brass alloy, m Pb represents the mass percentage of the Pb in the brass alloy.

3. The brass alloy according to claim 1, characterized in that The particle size of the C phase is 1nm-200nm.

4. A method for preparing the brass alloy according to any one of claims 1 to 3, characterized in that the steps include: After the raw materials, the graphene copper alloy, and the refiner are smelted, the materials are sequentially subjected to casting, single-hole extrusion, and stretching or drawing to obtain the brass alloy.

5. The preparation method according to claim 4, characterized in that the steps include: Step 1: After melting the processed recycled materials, graphene copper alloy, copper powder, arsenic ingots, antimony ingots, and copper iodide, the materials are slag-removed; Step 2: Take samples of the materials and perform component tests on the samples to determine whether the samples meet the following requirements: m Fe <0.1%,61.5%≤m Cu ≤63.5%,0.02%≤m As ≤0.15%,0.02%≤m Sb ≤0.1%,0.02%≤m I ≤0.1%,m Pb <0.2%; If not, add the corresponding materials and return to step 1; If satisfied, proceed to step 3; Step 3: adding a refining agent and refining the material; adding a refiner and refining the material; Step 4: sequentially subjecting the material to casting, single-hole extrusion, and stretching or drawing to obtain the brass alloy.

6. The preparation method according to claim 4 or 5, characterized in that: The mass percentage of graphene in the graphene copper alloy is 0.01%-2%.

7. The preparation method according to claim 4 or 5, characterized in that: The refiners include ammonium chloride, borax, ammonium carbonate, and potassium fluoroborate.

8. The preparation method according to claim 7, characterized in that: Calculated by mass percentage, the refiner includes: 10%-50% of ammonium chloride, 30%-50% of borax, 10%-50% of ammonium carbonate, and 5%-20% of potassium fluoroborate.

9. The preparation method according to claim 4 or 5, characterized in that: The extrusion ratio of the single hole extrusion process is 25-350.

10. The preparation method according to claim 4 or 5, characterized in that: The cooling water tank used in the single-hole extrusion process comprises: a tank body (1), and a water flow distribution plate (2) obliquely arranged inside the tank body (1); wherein: The bottom end of the trough body (1) is provided with a water inlet (11), the top end of the trough body (1) is provided with a water outlet (12), and a notch (13) connected to a single-hole extruder is provided on one side of the trough body (1) close to the water outlet (12); The water inlet (11) and the water outlet (12) are respectively arranged on two sides of the main body (1), and a water sealing ring (131) is arranged on the notch (13); The water flow uniform distribution plate (2) is a plate-shaped structure with a plurality of through holes evenly opened thereon, and the water flow uniform distribution plate (2) divides the interior of the tank body (1) into a first cavity (14) and a second cavity (15); The volume of the first cavity (14) is the same as the volume of the second cavity (15), the water inlet (11) is connected to the first cavity (14), the first cavity (14) is connected to the second cavity (15) through a plurality of through holes, and the second cavity (15) is connected to the water outlet (12); The brass alloy rod (0) obtained by the single-hole extruder enters the second cavity (15) through the notch (13) for cooling.